Blood Spectrum Biopsy as Screening Diagnostics of Health - Vladimir Dodtievich Bitsoev (Highlights on Medicine and Medical Research Vol. 3, 2021)
The work treats early diagnostics of diseases of internal organs and systems with the most up-to-date, unique, non-traumatic method, not requiring special skin preparation, the method of spectrum biopsy of blood from diagnostic projection zones of internal organs on human head, neck, and body.